UNIT 9.1 Conventional Light Microscopy. Issue 12 (2nd May 2016) - Cole, Eric S.
Abstract : In this molecular day and age, microscopy seems to be a neglected field of instruction. Too often professors, who themselves are strangers to the use of the light microscope, may hurry through a laboratory exercise designed to familiarize students with its uses. This chapter is designed to serve as a useful reference for instructors, perhaps demystifying some features of the microscope, and making their applications more user‐friendly and exciting. © 2016 by John Wiley & Sons, Inc.